2022
DOI: 10.7554/elife.73625
|View full text |Cite
|
Sign up to set email alerts
|

Brucella activates the host RIDD pathway to subvert BLOS1-directed immune defense

Abstract: The phagocytosis and destruction of pathogens in lysosomes constitute central elements of innate immune defense. Here, we show that Brucella, the causative agent of brucellosis, the most prevalent bacterial zoonosis globally, subverts this immune defense pathway by activating regulated IRE1α-dependent decay (RIDD) of Bloc1s1 mRNA encoding BLOS1, a protein that promotes endosome–lysosome fusion. RIDD-deficient cells and mice harboring a RIDD-incompetent variant of IRE1α were resistant to infection. Inactivation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…In addition to splicing the XBP1 transcript, activated IRE1α also degrades specific RNA species in a process called regulated IRE1α-dependent decay, or RIDD. Intriguingly, RIDD, which contributes to the intracellular survival of Brucella ( 28 ), influences the metabolism of cancer cells ( 52 ) and thus may also be affecting CAM metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to splicing the XBP1 transcript, activated IRE1α also degrades specific RNA species in a process called regulated IRE1α-dependent decay, or RIDD. Intriguingly, RIDD, which contributes to the intracellular survival of Brucella ( 28 ), influences the metabolism of cancer cells ( 52 ) and thus may also be affecting CAM metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Many intracellular pathogens induce ER stress in their host cells ( 20 , 21 ), including Brucella spp., which use their type IV secretion systems (T4SS) to interact extensively with the ER ( 22 ), ultimately leading to UPR activation ( 23 27 ). IRE1α has been shown to be phosphorylated upon Brucella infection ( 23 , 28 ) and to form puncta throughout infected cells ( 23 ). Though it is well established that IRE1α plays an important role in the development and effector functions of immune cells, the links between IRE1α activation and innate immunity remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to splicing the XBP1 transcript, activated IRE1α also degrades specific RNA species in a process called regulated IRE1α-dependent decay, or RIDD. Intriguingly, RIDD, which contributes to the intracellular survival of Brucella (28), influences the metabolism of cancer cells (52) and thus may also be affecting the metabolism of CAM.…”
Section: Discussionmentioning
confidence: 99%
“…Many intracellular pathogens induce ER stress in their host cells (20,21), including Brucella spp., which use their type IV secretion systems (T4SS) to interact extensively with the ER (22), ultimately leading to UPR activation (23)(24)(25)(26)(27). IRE1α has been shown to be phosphorylated upon Brucella infection (23,28) and to form puncta throughout infected cells (23). Though it is well established that IRE1α plays an important role in the development and effector functions of immune cells, the links between IRE1α activation and innate immunity remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have shown that GCN5L1 is involved in endosome-to-vacuole transport in Arabidopsis (Cui et al, 2010), the development of lysosome-related organelles in Zebrafish (Chen et al, 2018), and lysosomal trafficking in mouse liver (Wu et al, 2018). More recently, these endo-lysosomal processes have implicated GCN5L1 in the control of stress-related lysosomal positioning (Bae et al, 2019), LDL receptor recycling (Zhang et al, 2020), bacterial innate immune pathways (Wells et al, 2022), and hepatic lysosomal lipolysis (Wu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%